2021
DOI: 10.47067/ramss.v4i2.160
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Hesitancy and Associated Factors among Pakistani Population

Abstract: COVID-19 pandemic has caused global healthcare and economic crises and mass vaccination to acquire herd immunity seem to be the only solution. Present study aimed to evaluate the intent of Pakistani population towards vaccination and to uncover the barriers associated with vaccine reluctance. This cross-sectional study included responses of 855 Pakistani residents. Respondents’ knowledge of COVID-19 infection, intent of vaccination and barriers towards vaccine refusal were evaluated. Participants were categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…12 Another study assessing hesitancy to COVID vaccine among the general population in Pakistan by Ansar et al found prevalence of vaccine refusal to be 40%, which is higher than our study. 7 Part of the reason can be geographical differences, our study was primarily conducted in Punjab while the study by Ansar et al was primarily conducted in KPK.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…12 Another study assessing hesitancy to COVID vaccine among the general population in Pakistan by Ansar et al found prevalence of vaccine refusal to be 40%, which is higher than our study. 7 Part of the reason can be geographical differences, our study was primarily conducted in Punjab while the study by Ansar et al was primarily conducted in KPK.…”
Section: Discussionmentioning
confidence: 95%
“…6 Previous studies have shown that up to 40% of the population in Pakistan is reluctant in getting the COVID-19 vaccine. 7 This number is very drastic especially when compared to developed countries like USA where refusal to get the COVID-19 vaccine is present in 7%-15% of the population. 8 Myths such as the vaccine causes death and the vaccine is more harmful than the virus because it causes autism and infertility are excessively present in the Pakistani community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes about the seriousness of COVID-19 as a health issue were related to attitudes about its inevitability; those who thought it was a serious health issue were more likely to think they would inevitably contract COVID-19. An April 2021 convenience survey in Peshawar, Pakistan, found that 66% of persons thought COVID-19 was a serious health issue ( 32 ). We found 75.9% of persons thought it was a serious health issue.…”
Section: Discussionmentioning
confidence: 99%